1988
DOI: 10.1111/j.1530-0277.1988.tb00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Alcohol Treatment Results in Disturbed Vitamin D Metabolism and Skeletal Abnormalities in Rats

Abstract: The effect of chronic alcohol consumption on the skeleton was investigated in rats. The treated group received ethanol administered as 38% of caloric intake in a liquid diet (Sustacal) for 10 months. The control rats were pair weighted to the ethanol-treated animals throughout the study; the growth curves of the two groups were the same. The controls were given the same liquid diet except that dextrin:maltose (3:1) was substituted isocalorically for ethanol. Ethanol-treated rats did not differ from the pair-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
59
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 18 publications
(3 reference statements)
16
59
1
Order By: Relevance
“…A recent comprehensive study in alcoholic patients reported that nutritional status and low 1,25(OH) 2 D 3 plasma concentrations are independently related to increased prevalence of rib and vertebral fractures (Gonzá lez-Reimers et al, 2011). In rodent models, we and others have reported similar decreases in circulating 1,25(OH) 2 D 3 after chronic EtOH exposure (Turner et al, 1988;Keiver et al, 1996;Shankar et al, 2006). In addition, we have reported that this decrease in serum 1,25(OH) 2 D 3 is associated with a significant increase in renal CYP24A1, the enzyme responsible for the conversion of 1,25(OH) 2 D 3 to inactive 1,24,25-hydroxyvitamin D 3 metabolite (Shankar et al, 2008b).…”
Section: Introductionsupporting
confidence: 50%
See 1 more Smart Citation
“…A recent comprehensive study in alcoholic patients reported that nutritional status and low 1,25(OH) 2 D 3 plasma concentrations are independently related to increased prevalence of rib and vertebral fractures (Gonzá lez-Reimers et al, 2011). In rodent models, we and others have reported similar decreases in circulating 1,25(OH) 2 D 3 after chronic EtOH exposure (Turner et al, 1988;Keiver et al, 1996;Shankar et al, 2006). In addition, we have reported that this decrease in serum 1,25(OH) 2 D 3 is associated with a significant increase in renal CYP24A1, the enzyme responsible for the conversion of 1,25(OH) 2 D 3 to inactive 1,24,25-hydroxyvitamin D 3 metabolite (Shankar et al, 2008b).…”
Section: Introductionsupporting
confidence: 50%
“…In addition, we have reported that this decrease in serum 1,25(OH) 2 D 3 is associated with a significant increase in renal CYP24A1, the enzyme responsible for the conversion of 1,25(OH) 2 D 3 to inactive 1,24,25-hydroxyvitamin D 3 metabolite (Shankar et al, 2008b). It is noteworthy that we and others have also reported increases, decreases, or no change in serum concentrations of 25OHD 3 after EtOH consumption in rodents (Turner et al, 1988;Wezeman et al, 2007;Shankar et al, 2008b).…”
Section: Introductionmentioning
confidence: 81%
“…The detrimental effects on bone metabolism that we observed are consistent with earlier studies [39][40][41][42]. Alcohol is a potent inhibitor of bone growth in rats and decreases peak bone mass [39][40][41][42].…”
Section: Discussionsupporting
confidence: 92%
“…Similar reduction of plasma 1,25 dihydroxyvitamin D3 levels were also found in animal studies after chronic ethanol exposure (Turner et al 1988). Reduction of circulating vitamin D levels in alcohol abusers may lead to reduced bone mass and lower calcium levels (Sampson, 1997;Keiver and Weinberg, 2003).…”
Section: Vitamin Dsupporting
confidence: 63%